Analysis of the incidence of post-cholecystectomy diarrhea and its influencing factors in Hainan Province - Fengjiao Mao; Daya Zhang; Xianfeng Huang; Da Li; Wenrui Chen; Fan Zeng; Chen Chen; Shimei Huang; Yanting Lv; Yuliang Huang; Runyu Chen; Ying Mo; et al. (BMC Gastroenterology)
Abstract Background and aims Cholecystectomy is one of the most common surgical procedures for the treatment of diseases associated with gallstones, and the incidence of post-cholecystectomy diarrhea (PCD) has attracted attention in recent years. The aim of this study was to assess the prevalence of PCD in patients with gallstones and to analyze the factors influencing it. Methods Between August 2022 and December 2024, there were 3385 cases of gallstones diagnosed by abdominal ultrasound or CT examination and laparoscopic cholecystectomy in tertiary hospitals in Hainan Province. All participants in this study were followed up by telephone within 1 year postoperatively and by telephone survey using a standardized questionnaire. The incidence of PCD was calculated, and the relevant components of the follow-up were analyzed by one-way and multifactorial logistic regression using SPSS 26.0 statistical software. Results Four hundred seventy-nine patients (14.2%) developed PCD after undergoing laparoscopic cholecystectomy. Univariate analysis showed that age, BMI, dietary patterns, history of diabetes, alcohol consumption, gallstones and fatty liver disease were associated with the development of PCD ( P < 0.05). Binary logistic regression analysis showed that age (OR = 0.532, P = 0.010), BMI (OR = 40.615, P < 0.001), dietary patterns (OR = 0.635, P = 0.013), and history of diabetes (OR = 0.263, P < 0.001) were independent risk factors. Conclusion The incidence of PCD in Hainan Province is 14.2%. Over 50 years old, BMI, dietary pattern and history of diabetes were independent risk factors for the occurrence of PCD.